Influence of HCN channels on isolated heart functions in adult rats - A.M. Kuptsova; N.I. Ziyatdinova; L.I. Faskhutdinov; R.G. Biktemirova; T.L. Zefirov (Учёные записки Казанского университета: Серия Естественные науки)
Heart pacemaking has triggered a research interest for many decades. Hyperpolarization-activated currents (If) and ion channels (HCN channels) that provide this current are widespread in the central and peripheral nervous system. In atypical cardiomyocytes, HCN channels generate a spontaneous electrical activity. The physiological role of HCN channels in the working myocardium remains a subject of constant research. The expression of HCN channels in cardiomyocytes of the ventricles was shown. It is possible that If participates in the formation of the potential action of working cardiomyocytes and, consequently, in the regulation of the inotropic cardiac function. The study was performed in order to investigate the role of hyperpolarization-activated currents on chronotropy, inotropy, and coronary flow of the Langendorff heart in adult rats. Experiments ex vivo were performed on random-bred albino rats aged 20 weeks. The heart was perfused in the Langendorff System (ADInstruments). The coronary flow, left ventricular pressure, and heart rate were calculated along the curve. 10–9 – 3?10–5 М concentrations range of ZD7288 (Sigma) were used for If blockade. The analysis of the results demonstrated that the left ventricular pressure increased after the blockade of If at the concentration of 10–9 M and decreased with the blocker concentration of 3?10–5 M. The ZD7288 caused bradycardia of the isolated heart at the concentrations of 10–9, 10–6, 3?10–5 M. The isolated heart coronary flow decreased with the blockade of If at the concentration of 10–9 M and 3?10–5 M. It was concluded that If blockade changes chronotropy, inotropy, and coronary flow of the isolated heart in adult rats.